Wideband Printed Antenna Array Backed by Fractal AMC Surfaces for Wireless Communications - Malekpoor, Hossein (Current Approaches in Engineering Research and Technology Vol. 8, 2024)
A low-profile printed dipole antenna (PDA) array backed by broadband Giuseppe Peano fractal artificial magnetic conductors (AMC) with first and second iterations is introduced for wireless communications. It is known that the artificial magnetic conductor (AMC) structures introduce a privilege like a perfect magnetic conductor with an in-phase reflection response in a certain range. By integrating 4x4 AMC reflectors into the eight-element array with diverse polarizations, low-profile wideband printed structures with enhanced radiation properties are achieved. The proposed PDA, consisting of a pair of microstrip dipoles excited by an E-shaped microstrip feedline, extends the bandwidth range to 5.5-6.96 GHz (S11 \(\le\) -10 dB). The introduction of the first iteration of Giuseppe Peano fractal AMC surface as a reflector enhances the radiation efficiency. The PDA with the 4×4 Giuseppe Peano AMC array demonstrates a -10 dB measured impedance bandwidth from 4.25 to 7.10 GHz (50.2%) for WLAN and WiMAX applications. Compared to the PDA without AMC, the suggested PDA with AMC shows a size reduction of 50.5%, enhanced gain up to 8.2 dBi, and excellent impedance matching with uni-directional radiation patterns. The novel AMC unit cells, based on the first and second iterations of Giuseppe Peano fractal patches, operate at 6.10 GHz with an AMC bandwidth of 5.15-7.10 GHz (32%). Measured results indicate broad bandwidths from 4.2 to 7.10 GHz for all elements, with enhanced gains and good isolation between the elements for multiple-input multiple-output (MIMO) systems. By introducing the second iteration of the Giuseppe Peano fractal AMC compared to the first iteration, lower operating frequencies and consequently greater size reduction are achieved. It is concluded that the compact MIMO antenna array with high gains and efficiencies for elements can be used for WLAN and WiMAX applications.